Comparison of the effects of fixed and removable functional appliances on the skeletal and dentoalveolar structures - Bilgiç Fundagül; Hamamci Orhan; Başaran Güvenç (Sciendo, 2011)
Objective: To compare and analyse the effects of activator and Forsus FRD EZ appliances in the treatment of skeletal Class II division I malocclusion.